Robust dosimetric evaluation of FLASH proton beams using plane-parallel ionization chambers and EBT-XD films for pre-clinical studies - Heesoon Sheen; Sunghwan Ahn; Chanil Jeon; Youngyih Han; Changhoon Choi; Hee Chul Park; Daizo Amano; Nagaaki Kamiguchi; Sungkoo Cho (Nuclear Engineering and Technology, 2025)
This study established a robust methodology to evaluate the beam quality and dosimetric characteristics of FLASH-Proton beams. Dose plans were formulated for delivery of 3, 6, and 9 Gy at rates of 40 Gy/s and 70 Gy/s. The dosimetric evaluation employed two plane-parallel ionization chambers (ICs)—PPC-05 and Advanced Markus chamber—alongside EBT-XD film. Key parameters such as recombination and polarity effects of the ICs were measured, and the determined dose was quantified at predefined depths. Beam characteristics were further investigated using the EBT-XD film to corroborate IC findings. Polarity correction factors calculated for PPC-05 were 0.997 and 0.996 at 40 Gy/s and 70 Gy/s, respectively, with corresponding values for the Advanced Markus chamber of 1.0 and 0.999. The mean dose rates, derived from log files, were 52.3 Gy/s and 72.8 Gy/s for nominal rates of 40 Gy/s and 70 Gy/s, respectively. Depth dose profiles from the EBT-XD were analyzed at seven points and compared with measurements from PPC-05, revealing relative dose differences within ±5 % upon application of linear energy transfer correction. The established methodology is validated for routine clinical quality assurance.